Action-Specific Influences on Perception and Post-Perceptual Processes: Present Controversies and Future Directions - Philbeck, John W. (Psychol Bull, 2015)
The action-specific perception account holds that people perceive the environment in terms of their ability to act in it. In this view, for example, decreased ability to climb a hill due to fatigue makes the hill visually appear to be steeper. Though influential, this account has not been universally accepted, and in fact a heated controversy has emerged. The opposing view holds that action capability has little or no influence on perception. Heretofore, the debate has been quite polarized, with efforts largely being focused on supporting one view and dismantling the other. We argue here that polarized debate can impede scientific progress and that the search for similarities between two sides of a debate can sharpen the theoretical focus of both sides and illuminate important avenues for future research. In this paper, we present a synthetic review of this debate, drawing from the literatures of both approaches, to clarify both the surprising similarities and the core differences between them. We critically evaluate existing evidence, discuss possible mechanisms of action-specific effects, and make recommendations for future research. A primary focus of future work will involve not only the development of methods that guard against action-specific post-perceptual effects, but also development of concrete, well-constrained underlying mechanisms. The criteria for what constitutes acceptable control of post-perceptual effects and what constitutes an appropriately specific mechanism vary between approaches, and bridging this gap is a central challenge for future research.